Generalised Multiscale Finite Element Methods for the Simulation of Complex Flows - Urombo, Jack; Yadav, Anit Kumar; Chadha, Naresh Mohan (International journal of applied and computational mathematics, 2025)
A multiscale method to simulate complex (non-Newtonian) fluids is developed. The method combines techniques of dimension reduction by generating offline basis functions and corresponding function spaces. The basis are coupled together so the multiphysics describing the flow are captured. The simulation is performed on a function space that is constructed from a spectral decomposition of a transport equation derived from the model of the flow.